(untitled) (El Hilo de la Fabula, 2018)
In this paper, my aim is to consider Aristotle’s Poetics, its rereading and engaging in dialogue with López Pinciano and Schiller’s writings. The method and theoretical framework adopted are Hermeneutics (Gadamer, Ricoeur) and the Comparative Literature Theory (Bakhtin). The hypotheses are that Aristotle’s Poiesis is a way of knowing; Pinciano’s Poetry, a way of conveying; and Schiller’s Aesthetics, a form of freedom.